One‐pot synthesis of highly functionalized benzo [1, 3] thiazine from isocyanides, aniline, and heterocumulene via Cu‐catalyzed intramolecular C‐H activation reactions. Issue 11 (2nd July 2019) - Dastjerdi, Hossein F.; Nematpour, Manijeh; Rezaee, Elham; Jahani, Mehdi; Tabatabai, Sayyed A.
Abstract: A one‐pot synthesis of functionalized benzo thiazine derivatives via a Cu‐catalyzed, multicomponent reaction of isocyanides, aniline, and heterocumulenes in acetonitrile at room temperature was developed. Transition metal‐catalyzed activation of C‐H bonds under mild copper‐catalytic reaction conditions, using simple and available starting materials, also obtaining a pure product with high yield without applying column chromatography are the major advantages of the applied method among the other ones used for this purpose. The structures are confirmed spectroscopically ( 1 H‐ and 13 C‐NMR, IR, and EI‐MS) and through elemental analyses. Abstract :